2017
DOI: 10.1080/14786419.2017.1286479
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of essential oils in phytopathogenic and post-harvest fungi control

Abstract: Commercial thyme and lavender essential oils were analysed by GC/MS. Sixty-six compounds accounting for 98.6-99.6% of total essential oil were identified. Thymol (52.14 ± 0.21%), followed by p-cymene (32.24 ± 0.16%), carvacrol (3.71 ± 0.01%) and γ-terpinene (3.34 ± 0.02%), were the main compounds in thyme essential oil, while large amounts of oxygenated monoterpenes linalool acetate (37.07 ± 0.24%) and linalool (30.16 ± 0.06%) were found in lavender one. In vitro antifungal activity of the essential oils was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…Carvacrol and eugenol are the principal aromatic active components of oregano oil and clove oil, respectively, and have a wide spectrum antimicroorganism activity, preventing food from fungal spoilage and foodborne bacteria (Nostro et al, ). In vitro studies have showed that carvacrol and eugenol could inhibit the growth of Botrytis cinerea , Phytophthora cactorum , Cryphonectria parasitica , and Fusarium circinatum (Ochoavelasco, Navarrocruz, Veralópez, Palou, & Avilasosa, ; Santamarina et al, ). Carvacrol and eugenol exhibited high antifungal activity against R. stolonifer in vitro in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol and eugenol are the principal aromatic active components of oregano oil and clove oil, respectively, and have a wide spectrum antimicroorganism activity, preventing food from fungal spoilage and foodborne bacteria (Nostro et al, ). In vitro studies have showed that carvacrol and eugenol could inhibit the growth of Botrytis cinerea , Phytophthora cactorum , Cryphonectria parasitica , and Fusarium circinatum (Ochoavelasco, Navarrocruz, Veralópez, Palou, & Avilasosa, ; Santamarina et al, ). Carvacrol and eugenol exhibited high antifungal activity against R. stolonifer in vitro in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Use of EOs as natural and safer antifungal agents for fruits, vegetables and mushrooms also during their postharvest operations it is a very current option and of great interest. According to the study of Bill et al ., thyme essential oil vapors reduced the anthracnose disease incidence by up‐regulation of phenylalanine ammonia‐lyase (PAL) gene expression and at the same time led to down‐regulation of lipoxygenase (LOX) gene expression of two Avocado fruits variety prior to cold storage.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…Eugenol, the main compound in both essential oils, is a natural phenolic compound characterized, among a wide range of biological properties, by its antifungal activity; 16 in the year 2013 it was approved as a fungicide by the European Food Safety Authority (EFSA), (Reg. EU No.…”
Section: Discussionmentioning
confidence: 99%